CGIAR GENDER Platform - Plan of Work and Budget 2020 - CGIAR GENDER Platform (CGIAR GENDER Impact Platform, 2020)
Being the first year of the Platform, no changes are envisioned of the Theory of Change as outlined in the proposal. Specific activities, such as the Resource and Learning Hubs, identified from the ENGAGE proposal (led by IFPRI) will be integrated into the workplan of the GENDER Platform. The Platform envisages outputs being generated through three modules and associated work packages. The modules are synergistic and feed on each other. The development of capacities of researchers and partners in rigorous and high quality gender research for development will build on the methods and approaches developed by the Platform and beyond. Organizational culture change will enable effective integration of gender in agricultural research across CGIAR and its partners. The enhanced capacities along with cutting edge methods and effective and cross-sectoral partnerships will lead to generation of evidence to fill critical data gaps and inform policy to being about transformational change at scale.